2021
DOI: 10.1128/mbio.00764-21
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens Growth Pole Ring Protein: C Terminus and Internal Apolipoprotein Homologous Domains Are Essential for Function and Subcellular Localization

Abstract: The Agrobacterium growth pole ring (GPR) protein forms a hexameric ring at the growth pole (GP) that is essential for polar growth. GPR is large (2,115 amino acids) and contains 1,700 amino acids of continuous α-helices. To dissect potential GPR functional domains, we created deletions of regions with similarity to human apolipoprotein A-IV (396 amino acids), itself composed of α-helical domains. We also tested deletions of the GPR C terminus. Deletions were inducibly expressed as green fluorescent protein (GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Interestingly, the master cell division regulator CtrA ( Mann et al, 2016 ) was not downregulated ( Figure 6 and Supplementary Figure 4 ). On the other hand, genes such as pleC ( Kim et al, 2013 ), podZ ( Grangeon et al, 2017 ; Howell et al, 2017 ), popJ ( Fields et al, 2012 ; Anderson-Furgeson et al, 2016 ), divK, divJ ( Pini et al, 2013 ), and GPR ( Zupan et al, 2019 , 2021 ), participating in determination of asymmetric and unipolar growth, displayed normal expression levels in the cKD24 mutant. The downregulation in many genes for cell division suggests a major perturbation in cell division, which is consistent with the longer cell division times and cell division problems exhibited by the cKD24 mutant ( Figures 2 , 3 and Supplementary Movies 2 – 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the master cell division regulator CtrA ( Mann et al, 2016 ) was not downregulated ( Figure 6 and Supplementary Figure 4 ). On the other hand, genes such as pleC ( Kim et al, 2013 ), podZ ( Grangeon et al, 2017 ; Howell et al, 2017 ), popJ ( Fields et al, 2012 ; Anderson-Furgeson et al, 2016 ), divK, divJ ( Pini et al, 2013 ), and GPR ( Zupan et al, 2019 , 2021 ), participating in determination of asymmetric and unipolar growth, displayed normal expression levels in the cKD24 mutant. The downregulation in many genes for cell division suggests a major perturbation in cell division, which is consistent with the longer cell division times and cell division problems exhibited by the cKD24 mutant ( Figures 2 , 3 and Supplementary Movies 2 – 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite this caveat, the combination of changes observed is unusual among mutants affecting cell division in Rhizobiales. Regarding cell shape, round cells were detected upon depletion of GPR in A. tumefaciens ( Zupan et al, 2019 , 2021 ) or its ortholog ( rgsE ) in S. meliloti 1021 ( Krol et al, 2020 ), as well as upon elimination of cpdR in S. meliloti 1021 ( Kobayashi et al, 2009 ) or ntrY in S. meliloti GR4 ( Calatrava-Morales et al, 2017 ). A round cell phenotype has been described also in cells that overproduce RgsM in S. meliloti 1021 ( Schäper et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since all the replicons have the origins localized to the cell pole, one possibility is that polar organizer proteins interact with each origin separately and indirectly cluster the origins together. In A. tumefaciens , three such proteins are known: PodJ, PopZ, and GPR ( 13 18 , 20 ). We found that these polar organizers are not required for the colocalization or clustering of the origins, suggesting that ParB1-RepBs directly interact with each other and cluster together.…”
Section: Discussionmentioning
confidence: 99%
“…There are three proteins (GPR, PopZ, and PodJ) that are thought to serve as polar organizing proteins. At the growth pole, GPR and PopZ are both required for unipolar growth, cell shape, and normal cell division ( 13 18 ). Moreover, in the absence of PopZ, the origin of Ch1 (or ori1 ) disassociates from the new pole, indicating that PopZ anchors the origin to the new pole ( 14 ), likely through interaction with ParB1 protein ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Homologues were not detected in Ca. T. nelsonii's genomes nor did we find homologues to other known bacterial IFs [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115]. The homopolymer bactofilin, CcmA (pfam04519), an alternative to IFs in bacteria [116], has been found broadly across bacteria and is present in Ca.…”
Section: Ca T Nelsonii Also Has Bacterial Homologues To Other Eukaryo...mentioning
confidence: 99%